Relationship of anxiety level to religious motivation and academic performance among diocesan and SVD seminarians of Manila - Viegas, Francis Jacob (Animo Repository, 1994)
This descriptive study is undertaken to find out the anxiety level and the degree of religious motivation of the seminarians as well as to assess the relationship of their anxiety level to religious motivation and academic performance.The study was deemed important in improving the quality of life in the seminary. The subjects were 98 seminarians, 43 diocesans and 55 SVDs, from Manila. The instruments used to gather data were Filipino Adolescent Anxiety Scale (FAAS) and Religious Motivation Index (RMI). Descriptive statistics were used in this study to compute the anxiety level and degree of religious motivation. Five dimensions of FAAS were correlated with ten factors RMI and with academic grade scores. The results revealed the following:(a) The diocesans had high anxiety level and high religious motivation while the SVDs had low anxiety level and low religious motivation.(b) There was a significant relationship between anxiety level and religious motivation as well as anxiety level and academic performance.(c) Even after partialling out the effect of demographic variables, such as age, place of origin, type of school attended, parent's educational level and number of years in the seminary, the relationship of anxiety level to religious motivation and academic performance was significant. (d) The religious status (diocesan/religious) of the seminarians did not moderate the relationship between anxiety level and religious motivation while it added significantly to the relationship between anxiety level and academic performance. It was concluded that those who have high religious motivation experience high anxiety and high anxiety level is related to decrement in academic performance.